Effectiveness of alternative means for controlling pomegranate postharvest pathogens - Mincuzzi, Anna Maria; Sanzani, Simona Marianna; Caputo, Marika; D'Ambrosio, Pasquale; Palou, Lluís; Ragni, Marco; Ippolito, Antonio (ASHS, 2024)
Pomegranate (Punica granatum L.) cultivation in southern Italy has recently gained increasing interest due to putative beneficial effects on human health. Both, in the field and postharvest product losses, especially in organic fruit production, represent the chief concern for this high-priced chain. Main postharvest pomegranate diseases are caused by latent pathogens that infect pomegranates during blooming stage (Coniella granati, Alternaria spp., Botrytis spp.), and secondarily by wound pathogens (Penicillium spp., Talaromyces spp., and Aspergillus spp.) affecting fruit during processing from harvest until the end of storage and shelf life. The aim of this research was to test the in vitro effect of alternative control means already present on the market, suitable for controlling pomegranate postharvest pathogens. Particularly, the effectiveness of a red seaweeds extract, a plant protein hydrolysate, and a chitosan solution were compared to fludioxonil (chemical control) and water (not treated control) assessing the mean growth diameter reached by each fungal colony at the end of the incubation. Chitosan behaved as the most effective substance in controlling all postharvest pomegranate fungal pathogens. This work was conducted within the framework of the PRIMA StopMedWaste project, which is funded by PRIMA, a program supported by the European Union.